Does innovation stimulate employment? Evidence from China, France, Germany, and The Netherlands. (28th December 2018) - Hou, Jun; Huang, Can; Licht, Georg; Mairesse, Jacques; Mohnen, Pierre; Mulkay, Benoît; Peters, Bettina; Wu, Yilin; Zhao, Yanyun; Zhen, Feng
Abstract: This article tests whether product and process innovations increase employment in three European countries—France, Germany, and The Netherlands—and in the People's Republic of China on the basis of the same underlying theoretical framework and comparable harmonized micro data. The data pertain to the period 2002–2004 and cover the manufacturing and services industries in the three European countries, and to the period 1999–2006 and only the manufacturing industries in China. Process innovation does not play a significant role, whereas non-innovation-related efficiency improvements in the production of unchanged products tend to reduce employment. In contrast, product innovation stimulates employment, the compensation effect via increased demand dominating the displacement effect. The net effect of product innovation and the net growth in total employment are comparable in the two regions.